PENGARUH KECANDUAN GAME ONLINE TERHADAP PERILAKU KONSUMTIF SISWA PENGGUNA GAME ONLINE - Yusnizal Firdaus Yulia Pebrianti Titi Andriyani (JURNAL RISET TERAPAN AKUNTANSI, 2018)
Research Cooperation Program between Lecturer and Collegeans entitled The Impacts of Addiction ofOnline Games towards The Students’ Habit of Consumptivity (Research involving students in SMAN 1Palembang and SMAN 2 Palembang), is raising problems as mentioned; 1) calculating the ratio of the impacts of addiction of online games towards the students in SMAN 1 Palembang and SMAN 2Palembang’s habit of consumptivity. 2) Calculating how big the impact of online games addiction towards the habit of consumptivity of students in SMAN 1 Palembang and SMAN 2 Palembang. The methods used in this research is the percentage of correspondents’ answers to the questions provided in questionnaire. Score Index (SI) is used to find out the percentage of the answers by the correspondents.The data analysis used in this research is compiled by using the qualitative andquantitative data analysis. The results are; a) The ratio of the impacts of addiction of online gamestowards the students in SMAN 1 Palembang and SMAN 2 Palembang is classified as “Average” according to score interpretation, b) the impact of online games addiction towards the habit of consumptivity of students in SMAN 1 Palembang and SMAN 2 Palembangis classified as “Average”.